Orchestrating the fecal microbiota transplantation: Current technological advancements and potential biomedical application - Nigam, Manisha; Panwar, Abhaya Shikhar; Singh, Rahul Kunwar (Frontiers in Medical Technology, 2022)
Fecal microbiota transplantation (FMT) has been proved to be an effective treatment for gastrointestinal disorders caused due to microbial disbalance. Nowadays, this approach is being used to treat extragastrointestinal conditions like metabolic and neurological disorders, which are considered to have their provenance in microbial dysbiosis in the intestine. Even though case studies and clinical trials have demonstrated the potential of FMT in treating a variety of ailments, safety and ethical concerns must be answered before the technique is widely used to the community's overall benefit. From this perspective, it is not unexpected that techniques for altering gut microbiota may represent a form of medication whose potential has not yet been thoroughly addressed. This review intends to gather data on recent developments in FMT and its safety, constraints, and ethical considerations.